A kontrolling funkció széleskörű elterjedésének és fejlődésének szükségessége a közszférában - Tóth-Kmoskó, Éva (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
The goal of this article is to show my readers how important is to improve the public controlling function in order to achieve a conscious application of the modern economic methods in the public management area. The issue is that the financial resources of the state budget are limited; in this way we are able to compare the two existing sectors of this field identified as public and competitive sector. The comparison will demonstrate that there is an abundant need for the public sector to be more efficient and result oriented at all levels of the public finances. Basically, there are no or very limited use of holistic controlling activities in the public sector unlike in its competitive partner. What conclusion can be drawn from it? The answer is simple, „adaptation". The public sector needs to adopt more of the controlling function, methods and systems from the competitive sector. The results yield qualitative changes in the controlling field which include massive challenges and responibility for the next generation of the public controllers.